A review of carotid and vertebral artery dissection. (2nd April 2022) - Clark, Michael; Unnam, Sudhakar; Ghosh, Sandip
Abstract : Cervical artery dissection is a major cause of ischaemic stroke in young adults. The diagnosis can be challenging as some patients may present with seemingly benign symptoms such as a headache, neck pain or dizziness. However, the neurological sequelae of a transient ischaemic attack, vision loss or ischaemic stroke are potentially devastating. All hospital clinicians must be able to recognise this diagnosis and organise timely and appropriate investigations as antithrombotic treatment reduces the risk of stroke recurrence. This article reviews the literature to provide practical information for clinicians to recognise key risk factors and features of history and examination which should raise suspicion of cervical artery dissection. Diagnosis can now be made using the non-invasive, commonly available modalities of computed tomography angiography or magnetic resonance angiography. Timely treatment with antithrombotic agents is recommended to reduce the rate of an ischaemic stroke.